2009
DOI: 10.1111/j.1460-9568.2009.07004.x
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of cued fear memory involves a distinct form of depotentiation at cortical input synapses onto the lateral amygdala

Abstract: The amygdala is known to be a critical storage site of conditioned fear memory. Among the two major pathways to the lateral amygdala (LA), the cortical pathway is known to display a presynaptic long-term potentiation which is occluded with fear conditioning. Here we show that fear extinction results in a net depression of conditioning-induced potentiation at cortical input synapses onto the LA (C-LA synapses). Fear conditioning induced a significant potentiation of excitatory postsynaptic currents at C-LA syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 90 publications
(117 reference statements)
5
86
2
Order By: Relevance
“…3E-G). Collectively, these results suggest that the average LA ensemble activity represents updated CS-US association strength in reversible fear learning and maintains this representation beyond memory consolidation, consistent with previous reports (Maren, 2000;Hong et al, 2011).…”
Section: La Ensemble Activity Represents Updated Cs-us Association Stsupporting
confidence: 80%
See 2 more Smart Citations
“…3E-G). Collectively, these results suggest that the average LA ensemble activity represents updated CS-US association strength in reversible fear learning and maintains this representation beyond memory consolidation, consistent with previous reports (Maren, 2000;Hong et al, 2011).…”
Section: La Ensemble Activity Represents Updated Cs-us Association Stsupporting
confidence: 80%
“…These fear neurons amount to only 10ϳ30% of all the LA neurons, suggesting a rather sparse and restricted encoding of CS-US associations (Quirk et al, 1995;Repa et al, 2001;Han et al, 2007). In contrast, fear learninginduced synaptic potentiation has been observed in the general population of LA neurons (McKernan and Shinnick-Gallagher, 1997; Kim et al, 2007;Zhou et al, 2009), leading to the previously suggested possibility that the majority of LA neurons are strongly inhibited by GABAergic interneurons (Paré and Gaudreau, 1996) and are thus virtually undetectable by either in vivo recordings or immediate-early gene staining methods. Interestingly, a previous report demonstrated that targeted ablation of the ϳ15% of LA neurons that preferentially participated in learning can significantly impair auditory fear memory, whereas ablating a similarly sized random population had no effect (Han et al, 2009).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Thus, whereas regions such as the amygdala, hippocampus, or prefrontal cortex may allow for the inhibition of fear expression or the modulation of that inhibition (12,21), the primary olfactory sensory system likely plays a major role in the CS sensitivity and responsiveness following a learning event and its extinction. A growing body of literature suggests that alterations in synaptic transmission within the basolateral amygdala (BLA) play an important role in the suppression of conditioned fear following extinction learning (22,23); in fact, there is evidence of depotentiation of conditioning-related amygdala synaptic transmission that occurs following extinction training (24)(25)(26)(27). These data are in line with our observation that extinction reverses aspects of conditioning-related effects, although the contribution of regions such as the amygdala in the regulation of primary sensory system structural changes remains an important area for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdala LTP requires activation of N-methyl-D-aspartate (NMDA) subtype of the glutamate receptor, and extinction training leads to depotentiation of LTP by inducing AMPA receptor endocytosis [28]. Thus, fear conditioning and extinction are accompanied by an increase and decrease in synaptic activity in amygdale, respectively [29]. Density of dendritic spines was significantly increased in the fear conditioned group compared to the fear extinction group in BLA [30].…”
Section: Nature and Mechanisms Of Fear Extinction In The Adultmentioning
confidence: 94%